Considerations for collecting Japanese anime for academic libraries. (3rd October 2019) - Masuchika, Glenn
Abstract : Purpose: Too often, academic library selectors of DVDs purchase Japanese animation (anime) for their popularity without any further concern of their important contributions to the combined wealth of researches of an academic library. The purpose of this paper is to offer considerations for an academic selector to ponder before adding this particular type of animation. These considerations do not necessary pertain to the collection development considerations for selectors at public libraries. Design/methodology/approach: This paper will discuss the major problems of actively adding anime to an academic library, the present areas of concern, and will offer warnings and suggestions based on a conceptual framework of anime having true academic value. Findings: Anime cannot be chosen independently as if it has any apparently intrinsic value sui generis. Anime must be added concomitantly according to the collection development policies with other resources, especially DVDs, to create a full, rich and useful collection to scholars. Originality/value: Academic studies concerning anime and collection development for academic libraries are usually comprised of only long lists of suggested anime, with no further discussions about its implications to the general worth of an academic library. This paper offers no such lists. Instead, it offers considerations selectors must take into account before investing time and money adding anime to an academic library collection.